Theoretical limits for sensing through phase separation - Henry Alston; Mason Rouches; Arvind Murugan; Aleksandra M. Walczak; Thierry Mora (Proceedings of the National Academy of Sciences, 2026)
Biomolecular condensates form on timescales of seconds in cells upon environmental or compositional changes. Condensate formation is thus argued to act as a mechanism for sensing such changes and quickly initiating downstream processes, such as forming stress granules in response to heat stress and amplifying cyclic GMP-AMP synthase enzymatic activity upon detection of cytosolic DNA. Here, we study a dynamical model of droplet nucleation and growth to demonstrate how phase separation allows cells to discriminate small concentration differences on finite, biologically relevant timescales. We propose optimal sensing protocols, which use the sharp onset of phase separation. We show how, given experimentally measured rates, cells can achieve rapid and robust sensing of concentration differences of 1 % on a timescale of minutes, offering an alternative to classical biochemical mechanisms.